Particle transport phenomena in low temperature solids - Bargheer, M.; Schwentner, N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
We review different approaches to measure the transport of F atoms and ions in rare gas matrices and compare the experimental results to simulations. Static measurements on sandwich structures and co-doped matrices yield rather long travel ranges beyond 2 nm, in accord with early classical simulations which predict a channeling of the F atoms in rare gas matrices. Nonadiabatic simulations show a rapid energy loss, fast nonadiabatic dynamics and only short travel ranges of typically 1 unit cell. The rapid energy loss, fast nonadiabatic transitions and the timescale for direct dissociation ( 250 fs) are verified by fs-pump-probe experiments. It remains a challenge to account for the long-range migration when nonadiabatic processes are allowed in simulations, and to measure the long distance flights directly by ultrafast spectroscopy.